Public Awareness in Paying Land And Building Tax in Maesa Unima Sub-District, South Tondano District - Apeles Lexi Lonto,; Arie Supriati,; Marianus Landaiyo, (Technium Social Sciences Journal, 2023)
The reason for conducting this research is to decide the public's attention to paying land and building fees in the City of Maesa Unima, South Tondano Regency and there are factors that cause people in the City of Maesa Unima not to pay land and building fees. The methodology used in this study is a subjective illustration methodology. the information used is perception, interviews, documentation. The consequences of this review show that there is no public awareness in paying area and building fees in the City of Inn Maesa Unima, this can be seen from the elements that influence public awareness. Efforts by public authorities to provide understanding to residents of local areas to pay land and building fees are still low or less than ideal, causing setbacks for regions in carrying out their commitments.